Theoretical Perspectives on the Concept of Competition Law - Gričenė, Paulina (Teisė, 2025)
With the rapid evolution of the digital economy and the ongoing processes of globalisation, novel forms of conduct by economic operators are emerging – and some of these may infringe upon the EU competition law yet remain insufficiently examined. Considering the inherent uncertainty and the open-ended nature of the core concepts underpinning the EU competition law, this article seeks to explore two theoretical frameworks that may enhance the effective application of competition rules in a dynamic and rapidly transforming economic environment. Specifically, the analysis focuses on the concepts of autonomous law and responsive law as potential interpretative approaches. The study begins by examining these concepts through the lens of legal theory and proceeds to evaluate their relevance in the context of the EU competition law, whose objective is to govern an ever-evolving internal market. It argues that the adaptability afforded by the open-textured structure of EU competition law permits a flexible interpretation that can accommodate complex and shifting market realities – provided that such interpretation considers a plurality of objectives and the broader implications of legal reasoning. While this adaptive tendency is increasingly evident in the practice of EU institutions, it simultaneously raises concerns regarding legal certainty.